Hepatitis B knowledge among women of childbearing age in three slums in Mumbai: a cross-sectional survey. Issue 1 (December 2016) - Jha, Swati; Devaliya, Divyesh; Bergson, Susan; Desai, Shripad
Abstract Background More than 17 million people in India are chronically infected with the hepatitis B virus (HBV). Approximately one million of the 26 million children born in India annually will develop chronic HBV infection in the course of their lives. Studies have put the HBsAg prevalence rate among pregnant women in India between 0.9 % and 3.1, indicating a considerable need for public health interventions aimed at protecting their offspring from infection. The PAHAL project in Mumbai, India, conducted an HBV knowledge survey among women of childbearing age in three local slum communities preparatory to planning a comprehensive HBV education intervention targeting this population. Methods Female health workers approached all households in three designated slum neighborhoods: one each in the eastern suburbs (ES), western suburbs (WS) and Island City (IC). Female residents aged 18–45 were invited to participate in the study, and those who agreed to participate responded to a questionnaire that was administered in the form of an oral interview. The five sections of the questionnaire addressed demography, hepatitis B knowledge, personal risk related to hepatitis B, pregnancy and childbearing history, and the participant's most recent pregnancy. A descriptive statistical analysis was performed. Results Health workers submitted 6571 interview forms that were suitable for analysis (ES, 28 %; WS, 34 %; IC, 38 %). Large proportions of study participants were married (89 %), were not employed (94 %) and had completed less than 12 years of school (87 %). Only 240 (3.6 %) women answered yes when asked if they knew about hepatitis B. Among those women, there were high levels of accurate knowledge regarding some modes of hepatitis B transmission but low levels of accurate knowledge regarding other modes. Twenty-two percent of 739 women who had given birth within the previous 36 months reported that they had been tested for HBV during pregnancy. While 70 % of these women reported that their children had received three doses of hepatitis B vaccine, reported vaccination levels varied greatly across the three study areas. Conclusions Despite the availability of a safe HBV vaccine, which is free for newborns and infants in many parts of India, preventing mother-to-child transmission of HBV remains a major challenge. Low awareness of HBV among women of childbearing age in Mumbai-area slums indicates a need for educational interventions targeting this population.